Strategi Peningkatan Keselamatan dan Kesehatan Kerja pada Kepanduan di Pelabuhan Semayang PT. Pelindo Balikpapan - Andi Ningrat; Mutmainna Mutmainna; Rusnaedi Rusnaedi; Arif Fuddin Usman; Muslihati Muslihati (Fakultas Teknik Universitas Maritim AMNI Semarang, 2024)
This research delves into strategies aimed at enhancing occupational safety and health practices within pilotage operations at Semayang Port, operated by PT. Pelindo Balikpapan. Given the inherently high-risk nature of port activities, particularly pilotage, ensuring the safety and well-being of workers is paramount. This research is motivated by the imperative to curtail workplace incidents and bolster operational efficiency through the implementation of robust strategies. A SWOT analysis was employed to comprehensively assess the strengths, weaknesses, opportunities, and threats inherent in the port's existing occupational safety and health system. The findings of this analysis revealed that a 'Turn Around' strategy, situated in Quadrant II of the SWOT matrix, presents the most viable course of action. This strategy effectively leverages external opportunities to mitigate internal weaknesses, thereby optimizing the overall safety and health posture. By adopting the 'Turn Around' strategy, PT. Pelindo Balikpapan is poised to elevate the standards of occupational safety and health within its pilotage operations at Semayang Port. Consequently, this is expected to lead to a reduction in accidents and a commensurate improvement in overall operational performance.